2016
DOI: 10.1080/0309877x.2015.1117597
|View full text |Cite
|
Sign up to set email alerts
|

The impact of higher fees on psychology students’ reasons for attending university

Abstract: Usage of any items from the University of Cumbria's institutional repository 'Insight' must conform to the following fair usage guidelines.Any item and its associated metadata held in the University of Cumbria's institutional repository Insight (unless stated otherwise on the metadata record) may be copied, displayed or performed, and stored in line with the JISC fair dealing guidelines (available here) for educational and not-for-profit activities provided that• the authors, title and full bibliographic detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…This suggests that students are now not necessarily choosing degree subjects based on interest and are instead thinking about their career path as a focus. This is in line with findings highlighting the career-related motivations of students, particularly those paying higher fees [41], and their expectations regarding graduate employment [4].…”
Section: Employability Expectationssupporting
confidence: 89%
See 1 more Smart Citation
“…This suggests that students are now not necessarily choosing degree subjects based on interest and are instead thinking about their career path as a focus. This is in line with findings highlighting the career-related motivations of students, particularly those paying higher fees [41], and their expectations regarding graduate employment [4].…”
Section: Employability Expectationssupporting
confidence: 89%
“…This appears to support previous findings that the increased tuition fees has had little detriment on students' expectations of their HE experiences [4], rather the increased fees is increasing personal responsibility for learning, expecting more of themselves rather than of academic staff. It suggests a change in the way students are approaching their studying and a change in their motivations [41], whilst on the surface this would not necessarily have a negative impact on staff it depends on the way in which students believe staff should facilitate this.…”
Section: Approach To Studyingmentioning
confidence: 99%
“…This notion is likely to be exacerbated further with the introduction of the proposed Teaching Excellence Framework (TEF; Department for Business Innovation and Skills 2016) in UK HEIs. Whilst some research has found minimal support for the idea students are more demanding Kaye 2014a, 2014b;Kaye and Bates 2017), there is increased competition for HEIs to attract students (Jurkowitsch, Vignali and Kaufmann 2006). Thus, performance on the NSS, which is made publicly available, is considered a key metric to which HEIs are held accountable when providing a "service" to an ever-increasing 1 Tuition fees in England were first introduced in September 1998, and after numerous incremental increases across the years, finally reached a premium in September 2012 whereby institutions were able to charge up to £9000 a year.…”
Section: Current Context Of Higher Educationmentioning
confidence: 99%
“…Though many aspects of student life are routine research topics, studies exploring students’ reasons for entering higher education appear fewer in number (Round, , p. 9; Kennett et al ., , p. 65). This is somewhat surprising, because as Kaye and Bates () argue, ‘examining the main reasons for students attending higher education […] is one useful way of gaining insight into the decision‐making of students in their considerations of attending university’. This paper therefore aims to investigate motives for university enrolment, and takes as its focus students’ non‐economic reasons —i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Though many aspects of student life are routine research topics, studies exploring students' reasons for entering higher education appear fewer in number (Round, 2005, p. 9;Kennett et al, 2011, p. 65). This is somewhat surprising, because as Kaye and Bates (2016) argue, 'examining the main reasons for students attending higher education [. .…”
Section: Introductionmentioning
confidence: 99%